Administration of Fermented Averrhoa bilimbi L. Fruit Filtrate on Growth, Hematological, Intestinal, and Carcass Indices of Broilers - A. Pratama; I. Mareta; T. Yudiarti; H. I. Wahyuni; E. Widiastuti; S. Sugiharto (Tropical Animal Science Journal, 2021)
The study investigated the effects of administration of graded levels of fermented Averrhoa bilimbi L. fruit filtrate in drinking water on the growth performance, hematological variables, intestinal ecology, and carcass characteristics of broilers. The experiment was arranged based on a completely randomized design. Two hundred day-old-Lohmann broiler chicks were randomly assigned into 4 treatment groups, each consisting of 5 replications with 10 chicks in each replication. The treatments were administration of fermented A. bilimbi L. fruit filtrate through drinking water at concentrations of 0% (CONT), 0.5% (FAB05), 1.0% (FAB1), and 2.0% (FAB2). Blood was sampled on days 21 and 33, while intestinal segments and digesta were collected on day 33. Feed conversion ratio (FCR) was improved (p<0.05) with the increased concentrations of fermented filtrate in drinking water. Body weight, cumulative feed intake, and mortality of broilers were not affected by the treatments. On day 21, thrombocytes decreased (p<0.05) with the increased concentrations of fermented filtrate. On day 33, leukocytes and lymphocytes were lower (p<0.05) in treated chicks than in control. On day 21, the high-density lipoprotein (HDL) and aspartate aminotransferase (AST) increased (p<0.05) with the enhanced fermented filtrate concentrations. On day 33, creatinine and alanine aminotransferase (ALT) increased (p<0.05) following the increased fermented filtrate concentration in drinking water. Fermented fruit filtrate increased (p<0.05) jejunal villi height and ileal crypt depth. Fermented filtrate also resulted in higher (p<0.05) pH values of jejunum. The Enterobacteriaceae counts in the ileum decreased (p<0.05) with the increased fermented filtrate concentration in drinking water. Fermented fruit filtrate decreased (p<0.05) the liver and caeca weights and increased (p<0.05) the proventriculus weight. In conclusion, administration of 2% of fermented A. bilimbi L. fruit filtrate (pH 1.83) through drinking water improved FCR, physiological condition, and intestinal ecology of broilers. The addition of fermented fruit filtrate up to 2% in drinking water did not exert a negative effect on the carcass characteristics of broilers.